A brewed awakening : a novel - Basham, Pepper (Thomas Nelson, 2026)
"Daphne dreams of Mr. Darcy. Finn serves up pints and rock music. Can opposites attract when a tea shop princess meets her pub-owning rival?"-- Provided by publisher.